Step * 1 1 of Lemma rsum-telescopes2


1. : ℤ
2. {n...}
3. {n..m 1-} ⟶ ℝ
4. {n..m 1-} ⟶ ℝ
5. ∀i:{n..m-}. (x[i 1] y[i])
6. Σ{-(y[k]) -(x[k]) n≤k≤m} (-(y[m]) -(x[n]))
7. Σ{-(y[k]) -(x[k]) n≤k≤m} = Σ{x[k] y[k] n≤k≤m}
⊢ Σ{x[k] y[k] n≤k≤m} (x[n] y[m])
BY
(RWO  "-1" (-2) THENA Auto) }

1
1. : ℤ
2. {n...}
3. {n..m 1-} ⟶ ℝ
4. {n..m 1-} ⟶ ℝ
5. ∀i:{n..m-}. (x[i 1] y[i])
6. Σ{x[k] y[k] n≤k≤m} (-(y[m]) -(x[n]))
7. Σ{-(y[k]) -(x[k]) n≤k≤m} = Σ{x[k] y[k] n≤k≤m}
⊢ Σ{x[k] y[k] n≤k≤m} (x[n] y[m])


Latex:


Latex:

1.  n  :  \mBbbZ{}
2.  m  :  \{n...\}
3.  x  :  \{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
4.  y  :  \{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
5.  \mforall{}i:\{n..m\msupminus{}\}.  (x[i  +  1]  =  y[i])
6.  \mSigma{}\{-(y[k])  -  -(x[k])  |  n\mleq{}k\mleq{}m\}  =  (-(y[m])  -  -(x[n]))
7.  \mSigma{}\{-(y[k])  -  -(x[k])  |  n\mleq{}k\mleq{}m\}  =  \mSigma{}\{x[k]  -  y[k]  |  n\mleq{}k\mleq{}m\}
\mvdash{}  \mSigma{}\{x[k]  -  y[k]  |  n\mleq{}k\mleq{}m\}  =  (x[n]  -  y[m])


By


Latex:
(RWO    "-1"  (-2)  THENA  Auto)




Home Index